Evaluasi Kebijakan Transportasi Massal Kota Surabaya: Dampak Kegagalan Sterilisasi Jalur Prioritas terhadap Kinerja Waktu Tunggu Suroboyo Bus - Zidni Muntaha Ridho; Ratnasari Dewi Faradilla; Robi’atul Adawiyah; Putri Nendi Kirani; Kharisma Ilmi Alawy Wahbiyah; Tauran Tauran; Wilda Sumarsyah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to evaluate the implementation of the Suroboyo Bus priority lane sterilization policy in Corridor R1/R2 of Surabaya City. The existence of this mass transportation is expected to unravel urban traffic congestion, but operational reality on the ground shows a significant deviation in waiting times. The approach used is a descriptive qualitative research utilizing the public policy evaluation criteria from William N. Dunn, which includes effectiveness, adequacy, and responsiveness. Primary and secondary data collection was conducted through observation, in-depth interviews, and documentation studies. The research results prove that the policy implementation has not been effective because the fleet waiting time reaches 32 minutes, which exceeds the 15-minute service standard due to the loss of road space autonomy in mixed traffic. The adequacy level of the instrument is considered very weak because visual paint markings have failed to create a psychological deterrent effect without being balanced by the construction of physical barriers and law enforcement. This structural failure impacts the low responsiveness of services, which then triggers a crisis of trust and a shift in commuter behavior towards ride-hailing services. The researcher recommends tactical interventions in the form of integrated law enforcement, the installation of concrete physical separators, and the adoption of transit signal priority technology at intersections.